SUPPORTING DOCTORAL RESEARCH DEVELOPING CONCEPTUAL FRAMEWORK - Hussin, Hanipah; Wang , Jia; Wang , Qian; Hu, Shuoli; Zhou , Jiawei; Jin , Hua (Journal of Human Capital Development (JHCD), 2025)
ABSTRACT This paper provides a critical reflection on how a supervisor supporting doctoral students developing their conceptual framework. Issues and challenges in this paper are to instil some values on consideration of the role of conceptual frameworks in the doctoral research process. Inductive approach and participatory action research has been used as a methodology and research design. Research progress report and focus group interview used as a qualitative data collection technique. Through reflection on the fives authors’ own conceptual frameworks for their doctoral studies, a pedagogical model has been developed. It is needs for arrangement between variables and their characteristics, methodology and epistemology of doctoral research area of study. Finding show, that supervisor involves as a co-inquiry activities supported the extended abstract thinking essential at the level of doctoral research. Benefit of the pedagogical model ensure a conceptually valid research project and will focus the social and educational activities of the research process. The suggestion is supporting doctoral research in developing conceptual framework, and values their ideas and theories as a basic pillar. Good supervisory skills and close relationships are the evidences of pedagogical model in higher level of developing young academia in university. Keywords: Participatory action research, critical reflection, conceptual framework, supervisory, inductive approach